"Metabolically Healthy" Obesity and Hyperuricemia Increase Risk for Hypertension and Diabetes: 5‐year Japanese Cohort Study. Issue 11 (18th September 2017) - Kuwabara, Masanari; Kuwabara, Remi; Hisatome, Ichiro; Niwa, Koichiro; Roncal‐Jimenez, Carlos A.; Bjornstad, Petter; Andres‐Hernando, Ana; Sato, Yuka; Jensen, Thomas; Garcia, Gabriela; Ohno, Minoru; Hill, James O.; et al.
Abstract : Objective: Whether obesity without metabolic syndrome (i.e., "metabolically healthy" obesity) confers similar or less metabolic risk remains controversial. Methods: A retrospective 5‐year cohort study of 9, 721 Japanese subjects (48.5 ± 10.5 years, 4, 160 men) was conducted in 2004 and reevaluated 5 years later. Subjects were excluded if they were hypertensive or diabetic or were receiving medications for dyslipidemia and/or gout or hyperuricemia in 2004. Study subjects were categorized according to baseline BMI  ≥ 25 kg/m 2 (overweight/obesity) and < 25 kg/m 2 (lean/normal weight) and also whether they had metabolic syndrome. The cumulative incidence of hypertension and diabetes over 5 years between groups was assessed. A second analysis evaluated whether baseline hyperuricemia provided additional risk. Results: Subjects with overweight/obesity but without metabolic syndrome carried increased cumulative incidence of hypertension (14.6% vs. 7.2%, P  < 0.001) and diabetes (2.6% vs. 1.1%, P  = 0.004) over 5 years compared to lean/normal subjects without metabolic syndrome. Overweight/obesity conferred an increased risk for diabetes even in individuals with normal fasting blood glucose. Hyperuricemia became an independent risk factor for developing hypertension over 5 years in lean/normal subjects without metabolic syndrome. A 1 mg/dL increase in serum uric acid carried increased risk for hypertension (19%) and diabetes (27%). Conclusions: Metabolically healthy obesity and hyperuricemia confer increased risk for hypertension and diabetes.